2018
DOI: 10.1159/000491589
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work in Patients with Hematological Cancers 1 Year after Treatment: A Prospective Longitudinal Study

Abstract: Background: Although hematological cancer survivors have a high risk of disability, data on work-related issues are scarce for this population. Methods: We investigated return to work (RTW) and work ability (Work Ability Index, WAI) in hematological cancer patients 6 months and 1 year after cancer treatment. We explored associations between baseline sociodemographic and medical characteristics and RTW as well as work ability at follow-up. Results: The participation rate was 42% (baseline n = 91, after 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 19 publications
2
17
0
11
Order By: Relevance
“…Six (17%) of the included studies (Von Ah et al 2017Ah et al , 2018Ho et al 2018;Hartung et al 2018;Gregorowitsch et al 2019;Couwenberg et al 2020) used the complete Work Ability Index (WAI), a questionnaire that consists of seven items. These 7 items are (1) current work ability compared with the lifetime-best (on a scale of 0-10),…”
Section: Assessment Methods Used To Measure Work Abilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Six (17%) of the included studies (Von Ah et al 2017Ah et al , 2018Ho et al 2018;Hartung et al 2018;Gregorowitsch et al 2019;Couwenberg et al 2020) used the complete Work Ability Index (WAI), a questionnaire that consists of seven items. These 7 items are (1) current work ability compared with the lifetime-best (on a scale of 0-10),…”
Section: Assessment Methods Used To Measure Work Abilitymentioning
confidence: 99%
“…The 36 studies covered 12 (33%) longitudinal studies (De Boer et al 2008;Nieuwenhuijsen et al 2009;Bains et al 2012;Nilsson et al 2016;Doll et al 2016;Zanville et al 2016;Duijts et al 2017;Hartung et al 2018;Wolvers et al 2019;Gregorowitsch et al 2019;Tamminga et al 2019;Couwenberg et al 2020), six (17%) case-control studies Gudbergsson et al 2008aGudbergsson et al , 2011Lee et al 2008;Lindbohm et al 2012;Carlsen et al 2013), and 18 (50%) cross-sectional studies. Almost half of all included studies was published in 2017 or later.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of some other studies also show that although 64-84% of cancer survivors return to work after the initial treatment, a significant proportion of them return to work with disabilities and have a strong desire to quit their job or change it (De Boer et al, 2008). Also, the results of a longitudinal study by Hartung et al, (2018) showed that 6 months after the completion of the initial treatment, only 35% of the survivors returned to work, while 12 months after the initial treatment, this figure reached 58%. In a study by Dahl et al, (2016) which was performed on prostate cancer survivors, the results show that 74% of cancer survivors returned to work full-time and 19% part-time.…”
Section: Discussionmentioning
confidence: 84%
“…Dank verbesserter Behandlungsmethoden und höherer Überlebensraten wächst die Zahl derer, die trotz oder nach überstandener Krankheit ihren Beruf ausüben oder ihn wieder aufnehmen können [ 6 ]. Mittlerweile liegen aus Deutschland verschiedene wissenschaftliche Untersuchungen zu beruflichen Perspektiven von Krebspatient*innen vor, die sich allerdings aufgrund inhaltlicher und methodischer Unterschiede nur schwer vergleichen lassen [ 1 , 5 , 6 , 9 , 10 ]. Bei einer insgesamt noch übersichtlichen Datenlage lässt sich in der Tendenz Folgendes festhalten: Der größere Teil der Krebserkrankten im erwerbsfähigen Alter nimmt die Berufstätigkeit wieder auf – Reintegrationsquoten liegen in Deutschland zwischen 60 % und 65 % [ 1 , 9 ].…”
Section: Hintergrund Und Ausgangspunkteunclassified